LAYANAN SIRKULASI PERPUSTAKAAN DI MASA NEW NORMAL: UPAYA PUSTAKAWAN UNNES DALAM MENINGKATKAN JASA LAYANAN KEPADA PEMUSTAKA - ., Setyarini*; Handoyo, M.Z. Eko (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
The existence of a university library has a very important role in the process of transferring science and technology, as well as in supporting the activities of the Tri Dharma of Higher Education; research, teaching, and community service. In the current Covid-19 pandemic, it can be said that almost all libraries are also affected in providing services to librarians. Not a few libraries in the early days of the pandemic closed their services, as well as some that continued to open services virtually (digital / online). This situation had stopped for quite a long time. Then the situation moved to the New Normal era, where in this period the library began to adjust its situation, regarding its library service model. There are those who open services entirely online, where libraries do not open services in the form of library visits, there are also those that open online and offline with modifications at some of their service points. This also happened in the Semarang State University Library, which during the New Normal period opened its services gradually. The following article attempts to describe the library services of Semarang State University, more specifically in the section on circulation (borrowing and returning library materials (books).